2019
DOI: 10.1061/(asce)cc.1943-5614.0000950
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Retrofit Schemes with FRP for Deficient RC Beam-Column Joints: State-of-the-Art Review

Abstract: 8This paper aims to review and critically assess experimental research efforts on the seismic retrofit of 9 existing reinforced concrete (RC) beam-column joints with fibre-reinforced polymer (FRP) sheets of 10 the past 20 years. The review of the literature revealed several promising features of FRP 11 strengthening schemes. FRP retrofits can be used to address a number of different deficiencies in 12 non-seismically designed RC members framing into beam-column joints. A majority of studies 13 concentrate on j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…They are reported due to poor and inadequate detailing of the longitudinal and transverse reinforcement and to the use of smooth bars. Some experimental studies were carried out on evaluating and retrofitting existing RC building structures designed according to codes earlier than the 1970s [6,[17][18][19][20]. Most of these studies are related to ribbed bars.…”
Section: Seismic Behaviour Of Infilled Rc Structures: Definition Of Damage Typementioning
confidence: 99%
“…They are reported due to poor and inadequate detailing of the longitudinal and transverse reinforcement and to the use of smooth bars. Some experimental studies were carried out on evaluating and retrofitting existing RC building structures designed according to codes earlier than the 1970s [6,[17][18][19][20]. Most of these studies are related to ribbed bars.…”
Section: Seismic Behaviour Of Infilled Rc Structures: Definition Of Damage Typementioning
confidence: 99%
“…The response of beam-column joints is affected by a variety of parameters such as bond, shear load, confinement and fatigue, which are not yet well understood even independently, and they progressively reduce the joint's stiffness and strength. Therefore, the successful repair or strengthening of joints that have previously been damaged during cyclic loading caused by earthquakes is essential in order to enable the use of the affected structure again [14][15][16]. Detailed design recommendations have been introduced on the basis of the research and development of repair techniques in Europe and the United States in past decades [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve shear strengthening, various types of FRP exterior application shapes have been investigated, such as U-shaped [48][49][50][51][52][53], X-shaped [54][55][56] and T-shaped [57]. In addition to local strengthening of the joint area, others have attempted to improve the performance of the surrounding components, such as bond enhancement of the beam's bottom reinforcement bars [58][59][60], improvement of the columns' flexural performance and column confinement [16,[60][61][62][63][64]. The most common mode of failure in FRP-strengthened specimens that were tested was the debonding of FRP composites from the concrete surface.…”
Section: Introductionmentioning
confidence: 99%
“…In different designs [7][8][9][10][11][12], adding randomly distributed short fibers into the concrete matrix to improve the tensile and crack resistance is an excellent method [13][14][15][16][17][18][19]. Experiments showed that steel fiber had little contribution to compressive strength [20][21][22][23][24], but it can obviously improve the compressive behavior of stress and strain after cracking and also shows apparent toughness [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%